Original paper Estimation of vancomycin MIC for Staphylococcus aureus in patients treated in the Chair and Department of Dermatology, Poznan University of Medical Sciences - Tomczak, Hanna; Dańczak-Pazdrowska, Aleksandra; Horla, Anna; Duś-Żuchowska, Monika; Błażejewska, Wioleta; Polańska, Adriana; Okrutnik, Dominika (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2011)
Introduction : Staphylococcus aureus (S. aureus ) represents a significant aetiological factor in infections of skin and soft tissues. Resistance to vancomycin is very rare. In recent years the MIC creep phenomenon has been noted. At present, it is suggested that S. aureus strains with vancomycin minimal inhibitory concentration (MIC) at a level > 1 µg/ml poorly respond to treatment. Aim : The study was aimed to compare MIC evaluated in the automatic system of Vitek with the real MIC of vancomycin for S. aureus strains isolated from patients treated in the Department of Dermatology, Poznan University of Medical Sciences. Material and methods : Material for the studies involved 80 smears sampled from dermal lesions in patients diagnosed and treated in the Department of Dermatology, Poznan University of Medical Sciences in Poznan between May 2008 and December 2010. Results : Methicillin-sensitive S. aureus strains (MSSA) were isolated in 76 cases (95%), while methicillin-resistant S. aureus (MRSA) – in 4 cases (5%). Using the automatic Vitek technique in 72 cases (90%), the obtained vancomycin MIC for S. aureus amounted to ≤ 0.5 µg/ml, in 5 cases to 1 µg/ml and in 3 cases to 2 µg/ml. Using Etest technique, the real MIC amounted in one case to 0.5 µg/ml, in 1 case to 0.75 µg/ml, in 1 case to 1 µg/ml, in 19 cases to 1.5 µg/ml and in 58 cases to 2.0 µg/ml. Conclusions : Due to the MIC creep phenomenon and extensive diversities obtained in estimates of S. aureus resistance to vancomycin, the authors suggest estimating the real MIC.